2021
DOI: 10.1177/03093247211068770
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the sintering temperature, cooling time and grain size parameters to reduce residual stresses of copper-aluminum functionally graded material using response surface methodology

Abstract: One of the urgent needs for the medical, aerospace and military industries is to combine materials with heat-resistant as well as flexible structures. To create such a property, a ceramic must be placed next to metal. FGM materials have such a property in terms of thickness. Functionally graded materials (FGM) are examples of materials with different properties in the thickness direction. In the functionally graded materials, different properties can be created, by changing the percent weight of materials in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Gradual change in material properties across any geometrical direction resulted in the elimination of stress concentrations, fatigue, and corrosion. [1][2][3][4] FGMs withstand themselves in coarse environments without losing the characteristics of constituent elements and reduce their failure possibilities. Different material combinations, such as metal-ceramic, metalpolymer, ceramic-polymer, and metal-metal, having varied thermal expansion coefficients were developed as FGMs to attain different properties in a single component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gradual change in material properties across any geometrical direction resulted in the elimination of stress concentrations, fatigue, and corrosion. [1][2][3][4] FGMs withstand themselves in coarse environments without losing the characteristics of constituent elements and reduce their failure possibilities. Different material combinations, such as metal-ceramic, metalpolymer, ceramic-polymer, and metal-metal, having varied thermal expansion coefficients were developed as FGMs to attain different properties in a single component.…”
Section: Introductionmentioning
confidence: 99%
“…Few other works examined the acoustic impedance, residual stresses, and corrosion wear. 4,30,31 To the best of authors knowledge, no work was reported on tribological properties of Al-Cu FGM. Thus, present work is an attempt made to explore the erosion wear and abrasive wear behavior of Al-Cu MFGM fabricated through PM.…”
Section: Introductionmentioning
confidence: 99%